Análise retrospectiva linear de maxilas edêntulas por tomografia computadorizada feixe cônico - Bergamim, Macson (2014)
The aim of this study was to compare linear anatomic measurements of edentulous maxillary arches trying to correlate their different anatomic formats (square, taper, ovoid) to create a databank for biomechanical studies on implant dentistry. One hundred and two retrospective CBCT exams were retrospectively evaluated from the databank of one private radiology clinics. First, all maxillae were classified according to visual analysis (square, tapered, ovoid). After, the antero-posterior (AP- sagittal view), latero-lateral (TT- coronal view), and the arch perimeter (P-axial view) were obtained and evaluated using specific software (i-CAT Cone Beam 3D Dental Imaging System, Version 3.1.62, Xoran Technologies Inc., 2005). Percentages regarding each arch type were: square (36.27%, n=37), tapered (29.41%; n=30), and ovoid (34.31%, n=35). Linear measurements (mm) were as ollows: (square arch: P=108.43, T =52.49, AP= 46.93; tapered arch: P=107.24, TT= 51.27, AP=47.45, and e ovoid: P=107.89), TT=50.46), AP=47.73. No tatistically significant differences were observed among groups for each linear measurement. The square arch type presented the largest perimeter and TT distances. The ovoid type demonstrated a large AP distance value. Further combination of investigated linear measurements can provide new biomechanical insights for positioning and design of implantsupported prostheses